'But He Has Broken Every Jar in the Place, as He Said He Would …': Letters of Petrie to von Bissing: A Short Contribution to the History of Egyptology. Issue 1 (June 2019) - van Haarlem, Willem
The Archives of the Allard Pierson Museum in Amsterdam contain a stack of letters from W. M. Flinders Petrie to the German Egyptologist von Bissing, dating from between 1899 to 1911. Among other subjects, the letters refer to Petrie's conflict with the French excavator Amélineau, his rival for the concession at Abydos, asking von Bissing to keep an eye on him. Furthermore, Petrie gives short reports about his work in Abydos, Heracleopolis, the Fayum and Memphis, sometimes with otherwise unpublished details. Personal details, complaints on the bureaucracy of the Service des Antiquités are other important subjects occurring in the letters.